2022
DOI: 10.1186/s12890-022-02270-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of less invasive surfactant administration versus intubation-surfactant-extubation on bronchopulmonary dysplasia in preterm infants with respiratory distress syndrome: a single-center, retrospective study from China

Abstract: Background This study evaluated the effects of less invasive surfactant administration (LISA) and intubation-surfactant-extubation (InSurE) on bronchopulmonary dysplasia (BPD) in preterm infants with respiratory distress syndrome (RDS). Methods Neonates with respiratory distress syndrome requiring surfactant, with gestational age < 32 weeks and birth weight < 1500 g admitted to our neonatal intensive care unit from January 2018 to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Pareek et al also observed no statistically significant differences in major complication rates, duration of respiratory support, hospital stay, and mortality between LISA and InSurE groups ( 28 ). Likewise, Xu et al found no significant differences in the incidence of BPD, severity of BPD at 36 weeks postmenstrual age, and the rate of mechanical ventilation within 72 h after birth when comparing the LISA and InSurE groups ( 29 ). Therefore, the superiority of LISA over InSurE remains controversial.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Pareek et al also observed no statistically significant differences in major complication rates, duration of respiratory support, hospital stay, and mortality between LISA and InSurE groups ( 28 ). Likewise, Xu et al found no significant differences in the incidence of BPD, severity of BPD at 36 weeks postmenstrual age, and the rate of mechanical ventilation within 72 h after birth when comparing the LISA and InSurE groups ( 29 ). Therefore, the superiority of LISA over InSurE remains controversial.…”
Section: Discussionmentioning
confidence: 97%
“…We suspect that this difference in familiarity may have influenced the observed results. However, numerous studies have compared LISA and InSurE for preterm infants, and the findings suggest that there are no significant differences between these two approaches ( 26 29 ). Gupta et al found no disparities in the need for invasive mechanical ventilation in the first 72 h of life, hemodynamically significant PDA, IVH (>grade 2), BPD, and combined outcome of BPD/mortality when comparing MIST, which is used interchangeably with LISA, and InSurE ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations